The effect of budesonide on orthodontic induced root resorption - Hosseinagha Aghili; Seyed Amir Reza Fatahi Meybodi; Mohammed Danesh Ardekani; Mohammad Hassan Bemanianashkezari; Jalil Modaresi; Yousef Masomi; Mahdjoube Goldani Moghadam (Dental Research Journal, 2015)
Background: The aim of this study was to evaluate the hypothesis that budesonide increases the susceptibility of teeth to root resorption during the course of orthodontic treatment. Materials and Methods: A randomized controlled trial design (animal study) was employed. Budesonide was administered in test group for 14 days during which orthodontic force was applied to upper right molar. Afterwards, root resorption was measured on mesio-cervical and disto-apical parts of the mesial root on transverse histological sections. ANOVA and Bonfferoni tests were used. Statistical significance was considered to be P ≤ 0.05. Results: In general, the subgroups in which the force was applied showed significantly greater root resorption. Where force was applied there was no significant difference, whether budesonide was administered or not. While where there was no force, a group who received budesonide showed significantly greater root resorption than the other, unless at the coronal level where the difference was not significant. Conclusion: Within the limitations of this study, it seems budesonide could increase root resorption, but in the presence of orthodontic force this effect is negligible.